Dinamika Pemberdayaan Masyarakat Di Pesantren LDII Millenium Alfiena Nganjuk - Moh. Ashif Fuadi; Yunus Sulthonul Khakim (Prodi Sosiologi Agama, 2022)
This research discusses the existence of pesantren LDII Millennium Alfiena and its contributions. Based on existing problems, the author uses historical research methods that start by selecting topics, collecting historical sources, verifying sources, interpretations, and writing history. This writing focuses on primary sources in the form of documents or pesantren books, interviews, photos and support for previous research. This research concluded that Pesantren LDII Millenium Alfiena is an Islamic educational institution pioneered in 1996 by K.H. Seger Afandi Al-Khoir. The condition of pesantren in 1998 has given rise to the public's trust and the government to permit the establishment. So that pesantren LDII Millennium Alfiena and LDII in Lengkong can develop and gain social legitimacy with good praise. Social empowerment and cooperation with the government such as giving space to the community to sell in pesantren, village clean service work, normalization of residents' rivers, holding Forpimcam to establish friendship between the government and pesantren, planting trees with the Regent, and implementing the PPKM program as an implementation of government programs.